2004
DOI: 10.1080/1478994042000270274
|View full text |Cite
|
Sign up to set email alerts
|

Substance misuse in a high security hospital: Three years of urine drug testing at the State Hospital, Carstairs

Abstract: With the increasing evidence for the significant contribution to violence made by alcohol and drug misuse in people with mental disorder, there is emerging evidence of the importance and increasing prevalence of substance misuse problems in patients admitted to high security hospitals in the UK. Recorded routine voluntary urine drug screening of patients at the State Hospital, the high security hospital for Scotland and Northern Ireland, started in 1998. Results of urinalysis over the 3 years from 1 January 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Consider first the possibility of an increase in frequency of illness. In the four sites that were included in the present study and in many others (Brinded, 2000;Macintyre, McNamara, Irwin, Gray, & Darjee, 2004;Melzer et al, 2004;Mullen et al, 2000;Munk-Jorgenson, 1999;Nilsson & Persson, 1997;Schanda, Ortwein-Swoboda, Knecht, & Gruber, 2000;Taborda, Cardoso, & Morono, 2000;Taylor et al, 1998) most forensic beds are filled by men with schizophrenia or schizoaffective disorder. While a recent systematic review found no evidence of an increase in the incidence of schizophrenia, the most striking finding was the wide variation in incident rates across studies (McGrath et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Consider first the possibility of an increase in frequency of illness. In the four sites that were included in the present study and in many others (Brinded, 2000;Macintyre, McNamara, Irwin, Gray, & Darjee, 2004;Melzer et al, 2004;Mullen et al, 2000;Munk-Jorgenson, 1999;Nilsson & Persson, 1997;Schanda, Ortwein-Swoboda, Knecht, & Gruber, 2000;Taborda, Cardoso, & Morono, 2000;Taylor et al, 1998) most forensic beds are filled by men with schizophrenia or schizoaffective disorder. While a recent systematic review found no evidence of an increase in the incidence of schizophrenia, the most striking finding was the wide variation in incident rates across studies (McGrath et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…It was concerning that some staff appeared to be operating outside the hospital policy and conducting UDS under direct supervision. The ethical and legal position regarding mandatory UDS is not clear (MacIntyre et al . 2004), and it may be that these staff would not be supported legally should complaints occur.…”
Section: Discussionmentioning
confidence: 99%
“…2006), ease of adulteration (Kintz et al . 2006) and lack of accuracy (Kintz 1996, Macintyre et al . 2004, Levy et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations